H.761 Support of a New Syntax to Refer NCL-Node-Properties Instead of the Current "Take It From There" Syntax - Guedes, Alan L. V.; Colcher, Sergio (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Every NCL link relates two or more Node interfaces. When an NCL developer defi ne a link bind, however, it should always use BOTH component and interface attributes. This leads to two problems: (a) require defi ne two XML elements, which is tedious and error- prone; (b) require bad "Take It From There" workaround to access an interface from a Node participating in the link. We propose that component is optional. Then each interface can be accessed by an id which must be unique regarding the events of the same type in its container object. We propose a naming convention for identifying interfaces within a Document